A Theologian in His Workshop: Christopher Butler and The Downside Review. Issue 4 (October 2018) - Phillips, Peter
Butler honed his theological skills in a wide-ranging series of reviews and articles in the pages of The Downside Review, starting with his first review in 1931 and concluding with an article in 1966, the articles only drying up during the years that he had other demands on his time as Head Master in the school. He reviewed volumes of Biblical studies in French, German and English, and here laid the foundations of his work on the priority of Matthew. Strangely, two of the most important influences in his theological thinking are not dealt with in any detail here. For a discussion of the influence of Newman and of Lonergan, we have to look elsewhere. Nevertheless, there are also some very generous and open-minded reviews of works on the doctrine of the Church by non-Catholic writers, sewing the seeds of future important work in ecumenism.